Double-blinded randomized controlled trial to reveal the effects of Brazilian propolis intake on rheumatoid arthritis disease activity index; BeeDAI. - Yoshinari Matsumoto; Kanae Takahashi; Yuko Sugioka; Kentaro Inui; Tadashi Okano; Koji Mandai; Yutaro Yamada; Ayumi Shintani; Tatsuya Koike (PLoS ONE)
Background and aims Brazilian propolis reportedly contributed to suppressing disease activity in a mouse model of rheumatoid arthritis (RA), suggesting new treatment options using Brazilian propolis. However, only results from animal experiments have been available, and the suppressive effects of Brazilian propolis on disease activity in humans with RA remain unknown. The purpose of this study was to clinically validate how Brazilian propolis intake changes disease activity in RA patients. Methods This study was conducted as a multicenter, double-blinded, randomized, placebo-controlled, parallel-group study of 80 women with RA (median age, 61.5 years; interquartile range, 56.0 to 67.3 years) showing moderate disease activity on Disease Activity Score in 28 joints using erythrocyte sedimentation rate (DAS28-ESR). Test tablets containing Brazilian propolis were used in Group P (40 patients), and Brazilian propolis-free placebo tablets were used as control in Group C (40 patients). Group P received 5 tablets of propolis (508.5 mg of propolis) daily, and Group C received 5 tablets of placebo daily. The intervention lasted 24 weeks, with change in DAS28-ESR set as the primary endpoint. As secondary endpoints, other disease activity assessment (DAS28 using C-reactive protein, simplified disease activity index, clinical disease activity index), ultrasonographic evaluation of synovitis, activities of daily living, quality of life, changes in cytokine levels, and adverse events over the course of the study were also assessed. Data were statistically analyzed by analysis of covariance. Results No significant differences in the primary endpoint were identified between groups (Group P vs Group C, effect: 0.14, 95% confidence interval: -0.21 to 0.49, p = 0.427). Likewise, no significant differences were seen between groups for any secondary endpoints. The adverse event rate during the study period was 28% in Group P and 33% in Group C. Conclusions Brazilian propolis exerted no effects on disease activity in patients with RA.